Permutation Steganography for Polygonal Meshes Based on Coding Tree - Tu, Shihchun; Hsu, Hungwei; Tai, Wenkai (International Journal of Virtual Reality, 2010)
We propose a coding tree for permutation steganography in polygonal meshes. Instead of conceptually building a complete binary tree for remaining embedding/extracting primitives to encode/decode bitstream, our method lengthens bitstream by exploiting the coding tree of the primitives, a binary tree which is a little bit skewed. The coding tree has higher levels than the complete binary tree so that as experimental results show, the average capacity of our approach is more about 0.39 bit/vertex than that of Bogomjakov et al. [5], and the improvement of the maximal capacity comes up to 40% of Bogomjakov et al. [5]. Still, our method has the minimal capacity same with Bogomjakov et al. [5], and is simple and easy to implement as well. This ordering is obtained based on the mesh connectivity [14], making our method robust to geometric affine transformations. Also, the primitive rearrangement does not distort the cover media and cause suspicion of the hidden message